Ensuring equity: Pharmacogenetic implementation in rural and tribal communities - Leitch, Tianna M.; Killam, Shayna R.; Brown, Karen E.; Katseanes, Kirk C.; George, Kathleen M.; Schwanke, Corbin; Loveland, Joshua; Elias, Abdallah F.; Haney, Kerry; Krebsbach, Kate; Muzquiz, LeeAnna I.; Trinidad, Susan B.; et al. (Frontiers in Pharmacology, 2022)
Implementation strategies for pharmacogenetic testing have been largely limited to major academic medical centers and large health systems, threatening to exacerbate healthcare disparities for rural and tribal populations. There exists a need in Montana (United States)—a state where two-thirds of the population live in rural areas and with a large proportion of tribal residents—to develop novel strategies to make pharmacogenetic testing more broadly available. We established partnerships between University of Montana (UM) and three early adopter sites providing patient-centered care to historically neglected populations. We conducted 45 semi-structured interviews with key stakeholders at each site and solicited participant feedback on the utility of a centralized pharmacogenetic service at UM offering consultations to patients and providers statewide via telehealth. For settings serving rural patients—tribal and non-tribal—participants described healthcare facilities without adequate infrastructure, personnel, and funding to implement pharmacogenetic services. Participants serving tribal communities stressed the need for ethical practices for collecting biospecimens and returning genetic results to patients, largely due to historical and contemporary traumas experienced by tribal populations with regard to genetic research. Participants expressed that pharmacogenetic testing could benefit patients by achieving therapeutic benefit sooner, reducing the risk of side effects, and improving adherence outcomes for patients with limited access to follow-up services in remote areas. Others expressed concern that financial barriers to pharmacogenetic testing for patients of lower socioeconomic status would further exacerbate inequities in care. Participants valued the role of telehealth to deliver pharmacogenetic consults from a centralized service at UM, describing the ability to connect providers and patients to resources and expertise as imperative to driving successful pharmacogenetic implementation. Our results support strategies to improve access to pharmacogenetic testing for neglected patient populations and create opportunities to reduce existing healthcare inequities. By exploring critical challenges for pharmacogenetic implementation focused on serving underserved communities, this work can help guide equitable frameworks to serve as a model for other resource-limited settings looking to initiate pharmacogenetic testing.